1997
DOI: 10.1128/jb.179.8.2641-2650.1997
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro bioconversion of epsilon-rhodomycinone glycoside to doxorubicin: functions of DauP, DauK, and DoxA

Abstract: We recently determined the function of the gene product of Streptomyces sp. strain C5 doxA, a cytochrome P-450-like protein, to be daunorubicin C-14 hydroxylase (M. L. Dickens and W. R. Strohl, J. Bacteriol. 178: [3389][3390][3391][3392][3393][3394][3395] 1996). In the present study, we show that DoxA also catalyzes the hydroxylation of 13-deoxycarminomycin and 13-deoxydaunorubicin to 13-dihydrocarminomycin and 13-dihydrodaunorubicin, respectively, as well as oxidizing the 13-dihydro-anthracyclines to their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
79
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 46 publications
3
79
0
Order By: Relevance
“…1) (28). This is in contrast to the daunorubicin pathway, where the reaction order of the two enzymes DnrP and DnrK is more relaxed, as DnrK is able to methylate at least five biosynthetic intermediates (21).…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…1) (28). This is in contrast to the daunorubicin pathway, where the reaction order of the two enzymes DnrP and DnrK is more relaxed, as DnrK is able to methylate at least five biosynthetic intermediates (21).…”
mentioning
confidence: 60%
“…1) have been described as unstable and undergo spontaneous 10-decarboxylation on the rhodomycin and daunorubicin pathways, respectively (21,29). However, indirect evidence has suggested that the decarboxylation might also be enzymatically catalyzed by DnrP (21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RdmC shows about 50% sequence identity to related enzymes from other Streptomyces species, for instance DnrP from Streptomyces peucetius and DauP from Streptomyces sp strain C5 (17,18). These enzymes catalyze similar reactions, hydrolyzing 10-carbomethoxy-13-deoxycarminomycin to 10-carboxy-13-deoxycarminomycin (12,17). They all contain the same sequence motif G-X-S-X-G, typical for a serine hydrolase active site (18).…”
mentioning
confidence: 95%
“…DnrP from Streptomyces peucetius and DauP from Streptomyces sp. C5 exhibit sequence identities to RdmC of 51 and 53%, respectively (12,17). DnrP and DauP have both been proposed to act as 10-carbomethoxy-13-deoxycarminomycin esterases on anthracycline substrates removing the carboxymethyl side chain at the C-10 position of, for example, the rhodomycin D aglycones (DauP) (18).…”
Section: Quality Of the Electron Density Map And The Model-rdmcmentioning
confidence: 99%